ALTICA'S OBSIDIAN INDUSTRIES AND THEIR PLACE IN EARLY–MIDDLE FORMATIVE OBSIDIAN EXPLOITATION IN CENTRAL MEXICO. Issue 2 (2019) - Healan, Dan M.
Abstract: Survey and excavation conducted by Stoner and Nichols (2019) at Altica, located in the Basin of Mexico, recovered nearly 29, 000 pieces of obsidian, most of which apparently came from the nearby Otumba source. Formal classification followed by attribute analysis revealed a number of distinct lithic industries represented in the collection, although most are represented by finished objects that do not appear to have been produced on site. Most of the material consists of flakes probably used as unmodified, informal tools and produced on expedient cores consisting of some nodules but mostly percussion blades, spent cores, and other artifacts recycled as secondary cores. I propose that Altica acquired its obsidian from workshops possibly located in an area where they apparently existed in later times and may have during the Early–Middle Formative, as well. Virtually all of the obsidian in the collection appears to have been used for domestic or subsistence activities and was not involved in production or exchange systems believed to have existed at that time. Two unusual caches containing macronodules provide some evidence to the contrary, suggesting that Altica may have been a transshipment center.